2012
DOI: 10.1890/11-0948.1
|View full text |Cite
|
Sign up to set email alerts
|

Postdispersal seed predation limits the abundance of a long‐lived perennial forb (Lithospermum ruderale)

Abstract: Loss of seeds to consumers is common in plant communities, but the degree to which these losses influence plant abundance or population growth is often unclear. This is particularly the case for postdispersal seed predation by rodents, as most studies of rodent seed predation have focused on the sources of spatiotemporal variation in seed loss but not quantified the population consequences of this loss. In previous work we showed that seed predation by deer mice (Peromyscus maniculatus) substantially reduced s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 39 publications
(52 reference statements)
1
26
0
Order By: Relevance
“…seeded species, such as the one used in our study, are often seed-limited (Clark et al, 2007;Maron et al, 2012), suggesting that the patterns of granivory we observed may yield large-scale differences in the degree to which seed predation, rather than dispersal limitation or microsite limitation, affects the recruitment of some plant species (Orrock et al, 2006;Hillyer & Silman, 2010;Bricker & Maron, 2012;Maron et al, 2012;Germain et al, 2013). An additional implication of our findings is that future changes in climatic conditions may change the strength of plant-granivore interactions.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…seeded species, such as the one used in our study, are often seed-limited (Clark et al, 2007;Maron et al, 2012), suggesting that the patterns of granivory we observed may yield large-scale differences in the degree to which seed predation, rather than dispersal limitation or microsite limitation, affects the recruitment of some plant species (Orrock et al, 2006;Hillyer & Silman, 2010;Bricker & Maron, 2012;Maron et al, 2012;Germain et al, 2013). An additional implication of our findings is that future changes in climatic conditions may change the strength of plant-granivore interactions.…”
Section: Discussionmentioning
confidence: 64%
“…Granivory is an important plant-consumer interaction because the distribution and abundance of plants often hinges on the survival of their seeds (Crawley, 2000;Orrock et al, 2006;Clark et al, 2007;MacDougall & Wilson, 2007;Pearson et al, 2011;Bricker & Maron, 2012;Maron et al, 2012) and granivory can exert a strong influence over the diversity and composition of plant communities (e.g. Crawley, 2000;Howe & Brown, 2001;Pearson et al, 2011;Maron et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Seed traits largely determine rodent predation and dispersal that act as strong ecological filters in plant communities (Howe & Brown ; Pérez‐Ramos et al . ; Bricker & Maron ). Thus, nitrogen‐mediated changes in seeds quality might alter preferences of seed predators potentially leading to shifts in composition of plant communities.…”
Section: Discussionmentioning
confidence: 99%
“…; Miller et al . ; Bricker & Maron ), we combined data from the two interannual transitions, thus assuming no temporal variability. We fit the vital rate functions using generalised linear mixed‐effects models in a hierarchical Bayesian framework.…”
Section: Methodsmentioning
confidence: 99%